Avaliação do potencial citotóxico e indutor de EROs de Fruta-do-lobo (Solanum lycocarpum) - Peluco, Arthur Campoi (2022)
Solanum lycocarpum, a plant species from the Brazilian Cerrado, is the source of several plant derivatives used in studies that investigate the pharmacological properties and potential therapeutic use of that species. The present study had the general objective of investigating data in the literature about pharmacological actions and bioactive compounds identified in plant derivatives of the species S. lycocarpum, through a systematic bibliographical review. Furthermore, (i) cytotoxic effect of the alkaloid extract of S. lycocarpum fruits (EASL); (ii) production of reactive oxygen species (ROS) in cells of the macrophage-like lineage RAW 264.7, treated with EASL. RAW 264.7 cells, previously treated with different concentrations of EASL, were used in the cytotoxicity and ROS production assays. The cytotoxicity of the extract was measured through the quantification assay of the enzymatic activity of Lactate Dehydrogenase (LDH) in the supernatants of RAW 264.7 cell culture; ROS production was determined by treating the cells with the reagent 2',7'-dichlorofluorescein diacetate (DCFH-DA). The bibliographic review showed that this species contains bioactive compounds, especially glycoalkaloids (Solasodine, Solasonine, Solamargine), associated with important pharmacological actions, among them, antimicrobial. Experimental assays suggest that EASL (i) is not cytotoxic to RAW 264.7 cells; (ii) appears to inhibit LDH enzyme activity; (iii) does not induce ROS production in RAW 264.7 cells. Taken together, these data indicate that EASL has anti-inflammatory potential.